2004
DOI: 10.1111/j.1365-2265.2004.02050.x
|View full text |Cite
|
Sign up to set email alerts
|

Replacement therapy with levothyroxine plus triiodothyronine (bioavailable molar ratio 14 : 1) is not superior to thyroxine alone to improve well‐being and cognitive performance in hypothyroidism

Abstract: Replacement therapy of hypothyroidism with T4 plus T3 does not improve mood and cognitive performance compared to the standard T4 monotherapy. There is even a higher risk of signs of subclinical hyperthyroidism associated with impaired well-being of the patients, which is clearly caused by significant fluctuations in the steady-state fT3 serum concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
2
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 23 publications
4
112
2
8
Order By: Relevance
“…Based on Grozinsky-Glasberg et al 's (2006) metaanalysis and Ma et al's (2009) systematic review it can be summed up that combined T4 and T3 treatment does not improve well-being, cognitive function, or health status compared with T4 itself. This is proved with works by Appelhof et al, 2005;Clyde et al, 2003;Joffe et al, 2004;Meng et al, 2004;Nygaard et al, 2009;Regalbuto et al, 2007;Saravanan et al, 2005;Sawka et al, 2003;Siegmund et al, 2004;Valizadeh et al, 2009;Walsh et al, 2003 and others. Whereas first works signalled differences in favour of combined T4 and T3 (Bunevičius et al, 1999(Bunevičius et al, , 2002Bunevičius & Prange, 2000).…”
Section: Researches In Hypothyroidismsupporting
confidence: 62%
“…Based on Grozinsky-Glasberg et al 's (2006) metaanalysis and Ma et al's (2009) systematic review it can be summed up that combined T4 and T3 treatment does not improve well-being, cognitive function, or health status compared with T4 itself. This is proved with works by Appelhof et al, 2005;Clyde et al, 2003;Joffe et al, 2004;Meng et al, 2004;Nygaard et al, 2009;Regalbuto et al, 2007;Saravanan et al, 2005;Sawka et al, 2003;Siegmund et al, 2004;Valizadeh et al, 2009;Walsh et al, 2003 and others. Whereas first works signalled differences in favour of combined T4 and T3 (Bunevičius et al, 1999(Bunevičius et al, , 2002Bunevičius & Prange, 2000).…”
Section: Researches In Hypothyroidismsupporting
confidence: 62%
“…Several studies have recently reported that compared with levothyroxine alone, use of a combination of levothyroxine plus liothyronine produces no beneficial changes in cognitive performance in hypo-Effectiveness of thyroid supplement and tyrosine in Antarctica thyroid subjects (46)(47)(48). Other studies have reported moderate or no effects with T 4 supplementation (49,50).…”
Section: Discussionmentioning
confidence: 96%
“…Although no relation was observed in the meta-analysis between the percentages of included athyreotic patients and the effect of combination therapy on symptoms, it is preferable to restrict inclusion to spontaneous autoimmune hypothyroidism as was done in the present RCT (2). Six studies in the meta-analysis had a crossover study design (5,6,7,10,12,13), and five studies had a parallel study design (8,9,11,14,15). Observations in crossover studies are not independent because the same patients receive both combination and monotherapy (1).…”
Section: Randomized Controlled Trials: a Reappraisalmentioning
confidence: 99%
“…It follows that the serum FT 4 -FT 3 ratio is higher in T 4 -replaced hypothyroid patients than in controls. Indeed, the serum FT 4 -FT 3 ratio in patients randomized to receive T 4 monotherapy in the meta-analysis ranges from 4.0 to 6.7 (7,8,10,11,13), higher than the value of 3.3 observed in controls (18). The serum FT 4 -FT 3 ratio during combination therapy ranged from 2.2 to 4.8; in only two of the RCTs, the ratios (3.3 and 3.4 respectively) were close to control values, but both studies still failed to demonstrate superiority of combination therapy over monotherapy (7,13).…”
Section: Randomized Controlled Trials: a Reappraisalmentioning
confidence: 99%